Efficient kefiran production by Lactobacillus kefiranofaciens ATCC 43761 in submerged cultivation: Influence of osmotic stress and nonionic surfactants, and potential bioactivities - Daniel J. Dailin (Arabian Journal of Chemistry, 2020)
Kefiran is a water soluble polysaccharide produced by Lactobacillus kefiranofaciens ATCC 43761. It has wide potential applications in food, pharmaceutical and nutraceutical industries. To the best of our knowledge, there have been no previous reports on the effect of osmotic stress and ionic surfactants on kefiran production by L. kefiranofaciens ATCC 43761. Accordingly, the current work aimed at optimizing kefiran production as affected by osmotic stress and nonionic surfactants in submerged cultivation system. Afterwards, the work was extended to investigate cytotoxic as well as antioxidant potentials of kefiran. Firstly, different osmolarities, different ionic surfactants (Triton X-100, Tween 20, Tween 80) as well as their concentrations and addition time were evaluated. The kinetics of cell growth and kefiran production were evaluated before and after the addition of surfactants. Results clearly demonstrated that osmotic stress and surfactant addition had a stimulatory effect on kefiran production. Using the optimal medium osmolality, 550 mOsmol.kg−1, kefiran production was enhanced from 1.29 to about 1.38 g.L−1. Furthermore, Triton X-100 was found to be the best surfactant stimulating kefiran production when added at a concentration of 1.0 g.L−1 at the onset of cultivation process (0 h). This increased kefiran production from 1.38 g.L−1 to 1.62 g.L−1. To summarize, the maximal kefiran production can be enhanced using 550 mOsmol.kg−1 and by adding 1.0 g.L−1 of Triton X-100 at 0 h. The new optimized medium showed an increase of about 25.6% in kefiran production (1.29 up to 1.62 g.L−1). After this step, the process was further optimized in 16-L stirred tank bioreactor. Maximal kefiran production reached 2.32 g.L−1 and 1.87 g.L−1 in bioreactor under control and un-controlled pH conditions, respectively, corresponding to 72.9 and 45.0% increase from the initial production titer, respectively. The produced kefiran exhibited promising anticancer activity against breast cancer (MCF-7) cells, with an IC50 value of 193.89 μg.mL−1. Also, kefiran showed 96.58% radical scavenging activity at 100 μg/mL, with an ED50 recorded of 12.29 ± 0.98 μg.mL−1.